1998
DOI: 10.1590/s0101-81751998000400023
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Mirounga leonina Linnaeus (Pinnipedia, Phocidae) no extremo-sul do Brasil: agressão e patologias

Abstract: ABSTRACT. OCCURRENCE 01' MIROUNGA LEONINA LINNAEUS (PINNIPEDIA, PHOCIDAE) FROM SOUTIIERNMOST BRAZIL: INJURY AND PATIIOLOGIES. A male specimen of Mirolmga leonina Linnaeus, 1758 age estimated between 7-8 years old, collected at Santa Vitória do Palmar, Rio Grande do Sul State, southemmost Brazil (32°44' S and 53°22'W) is presented. Ali the skeleton was recovered except the rostral region. II shows an advanced osteomyelitis in the left dentary, extending from the synfisis until the middle portion ofthe body; as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Simões-Lopes and Ximenez (1990) reported two cases of human aggression toward Sotalia guianensis in the Baía Norte of Santa Catarina Island, where knife cuts and strikes were also the probable cause of death. Pinnipeds (seals and sea lions) in the southern region of Brazil are often shot at, victims of the conflict with fishermen (Rosas 1989;Drehmer et al 1998). Such retaliatory measure is usually related to competition for prey or damage to fishing gear.…”
Section: Discussionmentioning
confidence: 99%
“…Simões-Lopes and Ximenez (1990) reported two cases of human aggression toward Sotalia guianensis in the Baía Norte of Santa Catarina Island, where knife cuts and strikes were also the probable cause of death. Pinnipeds (seals and sea lions) in the southern region of Brazil are often shot at, victims of the conflict with fishermen (Rosas 1989;Drehmer et al 1998). Such retaliatory measure is usually related to competition for prey or damage to fishing gear.…”
Section: Discussionmentioning
confidence: 99%
“…Pinnipeds in general and otariids in particular, are naturally exposed to traumatic dental loss and dental pathologies (Drehmer and Ferigolo, 1996;Erb et al, 1996;Drehmer et al, 1998) due to several factors probably related to aggressive behavior (Campagna et al, 1988;Vila and Cassini, 1990). Indeed, natural tooth wear is characteristic for this species -typical for the inner surface of lower canines due to occlusion with upper ones -been more critical in older individuals.…”
Section: Extra Maxillary Teethmentioning
confidence: 99%
“…There are reports of osteomyelitis occurring in the oral region and the spine of Sotalia guianensis (van Bressem et al, 2007;Simões-Lopes et al, 2008), Orcinus orca (Linnaeus, 1758) (Kompanje, 1995c), Lagenorhynchus albirostris (Gray, 1846) (Kompanje, 1995b), Phocoena spinipinis Burmeister, 1865 (Montes et al, 2004), Globicephala melas (Traill, 1809) (Sweeney et al, 2005), Pontoporia blainvillei (Gervais & d'Orbigny, 1844) (Gerholdt, 2006), Delphinus capensis Gray, 1828 (Loch et al, 2011;van Bressem et al, 2007), Tursiops truncatus (Montagu, 1821) and Pseudorca crassidens (Owen, 1846) (van Bressem et al, 2007); Megaptera novaengliae (Borowski, 1781) (Felix et al, 2007). Kompange (1995c) suggested that dental injuries can function as a "gate" for infectious agents, since these infections are usually followed by penetrating wounds or fractures , or simply by normal wear and tear of the teeth that may eventually expose the pulp cavity, creating a mean of entry for infectious agents (Drehmer et al, 1998). The current study represents the first report of osteomyelitis occurring in Sotalia fluviatilis.…”
Section: Resultsmentioning
confidence: 67%